PENGARUH STRATEGI WANKAT-OREOVOCZ TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA SMPK IMMANUEL 2 SUNGAI RAYA - Yohana Dwi Kristiani Sinaga; Ade Mirza; Asep Nursangaji (Universitas Tanjungpura, 2020)
AbstractThis research aims to know the effect of the application of the Wankat-Oreovocz strategy to the ability of problem solving and activity of students in the form of algebra at the Christian Junior High School of Immanuel 2 Sungai Raya. This experimental method is experimental with a one-shot study and to collect data in this study used the problem solving test, along with the observation sheet of learning implementation and students learning activity. The participants in this study was 43 students of the VII B. The result showed that: 1) The Wankat-Oreovocz learning strategy didn't positively effect the students problem solving skill with the value of sig. 0.147; 2) The average of the application of the Wankat-Oreovocz strategy is well categorized with score of 3.20; 3) Students learning activity during the implementation of this strategy was in the category of very active with the percentage of 88.87%.Keywords: Wankat-Oreovocz Strategy, Problem SolvingPENDAHULUANMatematika merupakan suatu mata pelajaran yang